Pengaruh Penerapan E-Modul Kimia Berbasis Cooperative Learning Type NHT Pada Pembelajaran Ikatan Kimia Kelas X SMA - Yovanka Melinda Samosir; Bajoka Nainggolan (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to (1) find out whether the increase in student learning outcomes with the application of cooperative-based e-modules of the NHT type is higher than the learning of NHT chemistry with student reference teaching materials. (2) find out whether there is an effect of the application of e-modules based on cooperative types of chemistry. NHT on student learning outcomes. This research was carried out at the Harapan Baru Private High School Medan in November-December 2021. From the results of the study, the average pretest score for the experimental class was 36 and the control was 28,167. While the posttest average value of the experimental class was 82,667 and the control class was 77.5. The chemical normalized N-Gain value of the experimental class students was higher than the control class, namely 0.7254> 0.685 or based on the N-Gain percentage, which was 72.54% for the experimental class and 68.5% for the control class. The difference from the increase in learning outcomes from the two classes, namely 4.09%, it can be said that the application of the NHT cooperative-based chemistry e-module with student reference learning media on chemistry. In the hypothesis test, namely the t-test of one party (right side) at a significance level of 0.05, it is obtained that t_count > t_table which is 3,004> 2,002 then Ha is accepted and Ho is rejected. Thus, it can be said that there is an effect of applying cooperative-based chemistry e-modules on student chemistry learning outcomes in chemistry.